Lies Without Liars? Janus Capital and Conservative Securities Jurisprudence - Donald C. Langevoort (Washington University Law Review, 2013)
In Janus Capital Group, Inc. v. First Derivative Traders, the Supreme Court held that even if a mutual fund advisory firm had caused a lie about its late trading and market timing policies to appear in a prospectus issued by a mutual fund that it managed, it did not make a misrepresentation within the meaning of Rule 10b-5 because the prospectus in which the lie appeared was filed by and in the name of the mutual fund, not the adviser. According to the Court, the word “make” in Rule 10b-5 refers only to a statement by the person with ultimate legal authority over the filing and public dissemination of the document. In so holding, Justice Clarence Thomas and the rest of the majority joined a seemingly short list of judges who suggest that legal formalism is a particularly good weapon with which to fight securities fraud. Part I analyzes Janus’s interpretive methodology, arguing that it is more persuasive even within a faithfully conservative textualist framework if read as addressing only the implied private right of action under Rule 10b-5, not SEC enforcement proceedings or criminal prosecutions. Part II then traces the route to Janus in terms of precedent— both the more recent cases defining secondary liability and the early battles over the text of the “in connection with” requirement under Rule 10b-5. It claims that there are underappreciated historical links between secondary liability and the “in connection with” language, and that Janus is likely to prompt a reexamination of the scope of that language, too, at least as applied in private litigation. Part III surveys the open questions that are being litigated after Janus, such as how to address liability where there is no obvious sense of “authority” over more informal corporate publicity, what scheme liability means apart from making particular misstatements, and how to address cases where the deception was not directly aimed at investors but instead targeted at other parties, such as auditors or independent directors on an audit committee. Part IV offers a brief conclusion.
Keywords: securities; securities fraud; Rule 10b-5; Janus Capital Group; Inc. v. First Derivative Traders; Janus; legal formalism